Type I Error And Power Rates Of Robust Methods With Variable Trimmed Mean - Yusof, Zahayu Md (2010)
The effects of nonnormality and heteroscedasticity on the T1 and trimmed F (Ft) test statistics were investigated using two methods of trimming namely the proposed automatic trimmed mean and the typical fixed amount of trimming. These are typical problems in any test of equality of central tendency measure. For each test statistic, three automatic trimming procedures using different scale estimators MADn, Tn, and LMSn, and a fixed trimmed mean procedure were examined for their robustness via Type I error and power rates.